47d9c34bcce5578c363b0fbe551736e7e441864b
[lambda.git] / week4.mdwn
1 [[!toc]]
2
3 #These notes return to the topic of fixed point combiantors for one more return to the topic of fixed point combinators#
4
5 Q: How do you know that every term in the untyped lambda calculus has
6 a fixed point?
7
8 A: That's easy: let `T` be an arbitrary term in the lambda calculus.  If
9 `T` has a fixed point, then there exists some `X` such that `X <~~>
10 TX` (that's what it means to *have* a fixed point).
11
12    let W = \x.T(xx) in
13    let X = WW in
14    X = WW = (\x.T(xx))W = T(WW) = TX
15
16 Q: How do you know that for any term T, YT is a fixed point of T?
17
18 A: Note that in the proof given in the previous answer, we chose `T`
19 and then set `X = WW = (\x.T(xx))(\x.T(xx))`.  If we abstract over
20 `T`, we get the Y combinator, `\T.(\x.T(xx))(\x.T(xx))`.  No matter
21 what argument `T` we feed Y, it returns some `X` that is a fixed point
22 of `T`, by the reasoning in the previous answer.
23
24 Q: So if every term has a fixed point, even Y has fixed point.
25
26 A: Right:
27
28     let Y = \T.(\x.T(xx))(\x.T(xx)) in
29     Y Y = \T.(\x.T(xx))(\x.T(xx)) Y
30         = (\x.Y(xx))(\x.Y(xx))
31         = Y((\x.Y(xx))(\x.Y(xx)))
32         = Y(Y((\x.Y(xx))(\x.Y(xx))))
33         = Y(Y(Y(...(Y(YY))...)))
34
35 Q: Ouch!  Stop hurting my brain.
36
37 A: Let's come at it from the direction of arithmetic.  Recall that we
38 claimed that even `succ`---the function that added one to any
39 number---had a fixed point.  How could there be an X such that X = X+1?
40 Then
41
42     X = succ X = succ (succ X) = succ (succ (succ (X))) = succ (... (succ X)...)
43
44 In other words, the fixed point of `succ` is a term that is its own
45 successor.  Let's just check that `X = succ X`:
46
47     let succ = \n s z. s (n s z) in
48     let X = (\x.succ(xx))(\x.succ(xx)) in
49     succ X 
50       = succ ((\x.succ(xx))(\x.succ(xx))) 
51       = succ (succ ((\x.succ(xx))(\x.succ(xx))))
52       = succ (succ X)
53
54 You should see the close similarity with YY here.
55
56 Q. So `Y` applied to `succ` returns infinity!
57
58 A. Yes!  Let's see why it makes sense to think of `Y succ` as a Church
59 numeral:
60
61       [same definitions]
62       succ X
63       = (\n s z. s (n s z)) X 
64       = \s z. s (X s z)
65       = succ (\s z. s (X s z)) ; using fixed-point reasoning
66       = \s z. s ([succ (\s z. s (X s z))] s z)
67       = \s z. s ([\s z. s ([succ (\s z. s (X s z))] s z)] s z)
68       = \s z. s (s (succ (\s z. s (X s z))))
69
70 So `succ X` looks like a numeral: it takes two arguments, `s` and `z`,
71 and returns a sequence of nested applications of `s`...
72
73 You should be able to prove that `add 2 (Y succ) <~~> Y succ`,
74 likewise for `mult`, `minus`, `pow`.  What happens if we try `minus (Y
75 succ)(Y succ)`?  What would you expect infinity minus infinity to be?
76 (Hint: choose your evaluation strategy so that you add two `s`s to the
77 first number for every `s` that you add to the second number.)
78
79 This is amazing, by the way: we're proving things about a term that
80 represents arithmetic infinity.  It's important to bear in mind the
81 simplest term in question is not infinite:
82
83      Y succ = (\f.(\x.f(xx))(\x.f(xx)))(\n s z. s (n s z))
84
85 The way that infinity enters into the picture is that this term has
86 no normal form: no matter how many times we perform beta reduction,
87 there will always be an opportunity for more beta reduction.  (Lather,
88 rinse, repeat!)
89
90 Q. That reminds me, what about [[evaluation order]]?
91
92 A. For a recursive function that has a well-behaved base case, such as
93 the factorial function, evaluation order is crucial.  In the following
94 computation, we will arrive at a normal form.  Watch for the moment at
95 which we have to make a choice about which beta reduction to perform
96 next: one choice leads to a normal form, the other choice leads to
97 endless reduction:
98
99     let prefac = \f n. isZero n 1 (mult n (f (pred n))) in
100     let fac = Y prefac in
101     fac 2
102        = [(\f.(\x.f(xx))(\x.f(xx))) prefac] 2
103        = [(\x.prefac(xx))(\x.prefac(xx))] 2
104        = [prefac((\x.prefac(xx))(\x.prefac(xx)))] 2
105        = [prefac(prefac((\x.prefac(xx))(\x.prefac(xx))))] 2
106        = [(\f n. isZero n 1 (mult n (f (pred n))))
107           (prefac((\x.prefac(xx))(\x.prefac(xx))))] 2
108        = [\n. isZero n 1 (mult n ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred n)))] 2
109        = isZero 2 1 (mult 2 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred 2)))
110        = mult 2 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] 1)
111        ...
112        = mult 2 (mult 1 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] 0))
113        = mult 2 (mult 1 (isZero 0 1 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred 0))))
114        = mult 2 (mult 1 1)
115        = mult 2 1
116        = 2
117
118 The crucial step is the third from the last.  We have our choice of
119 either evaluating the test `isZero 0 1 ...`, which evaluates to `1`,
120 or we can evaluate the `Y` pump, `(\x.prefac(xx))(\x.prefac(xx))`, to
121 produce another copy of `prefac`.  If we postpone evaluting the
122 `isZero` test, we'll pump out copy after copy of `prefac`, and never
123 realize that we've bottomed out in the recursion.  But if we adopt a
124 leftmost/call by name/normal order evaluation strategy, we'll always
125 start with the isZero predicate, and only produce a fresh copy of
126 `prefac` if we are forced to. 
127
128 Q.  You claimed that the Ackerman function couldn't be implemented
129 using our primitive recursion techniques (such as the techniques that
130 allow us to define addition and multiplication).  But you haven't
131 shown that it is possible to define the Ackerman function using full
132 recursion.
133
134 A. OK:
135   
136 <pre>
137 A(m,n) =
138     | when m == 0 -> n + 1
139     | else when n == 0 -> A(m-1,1)
140     | else -> A(m-1, A(m,n-1))
141
142 let A = Y (\A m n. isZero m (succ n) (isZero n (A (pred m) 1) (A (pred m) (A m (pred n))))) in
143 </pre>
144
145 For instance,
146
147     A 1 2
148     = A 0 (A 1 1)
149     = A 0 (A 0 (A 1 0))
150     = A 0 (A 0 (A 0 1))
151     = A 0 (A 0 2)
152     = A 0 3
153     = 4
154
155 A 1 x is to A 0 x as addition is to the successor function;
156 A 2 x is to A 1 x as multiplication is to addition;
157 A 3 x is to A 2 x as exponentiation is to multiplication---
158 so A 4 x is to A 3 x as super-exponentiation is to exponentiation...
159